The impact of subsidized health insurance on the poor in Colombia: Evaluating the case of Medellın (2011)
This paper uses count and binary data models with an endogenous dummy variable, and propensity score matching to evaluate the effect of the subsidized health care program in Medellin (Colombia). The subsidized program, which primarily covers poor people, is found to have neither a significant impact on the use of preventive medical care nor hospitalization. However, parametric specification of preventive utilization indicates that there is both selection and moral hazard, effects that compensated approximately. These facts imply that the program can improve its coverage if mechanisms are created to lower the individual moral hazard effect.